2019
DOI: 10.4236/jbnb.2019.104010
|View full text |Cite
|
Sign up to set email alerts
|

Bioreactivity of Stent Material: <i>In Vitro</i> Impact of New Twinning-Induced Plasticity Steel on Platelet Activation

Abstract: A current challenge concerns developing new bioresorbable stents that combine optimal mechanical properties and biodegradation rates with limited thrombogenicity. In this context, twinning-induced plasticity (TWIP) steels are good material candidates. In this work, the hemocompatibility of a new TWIP steel was studied in vitro via hemolysis and platelet activation assessments. Cobalt chromium (CoCr) L605 alloy, pure iron (Fe), and magnesium (Mg) WE43 alloy were similarly studied for comparison. No hemolysis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…Hemocompatibility tests showed that the studied TWIP steels have similar performances to those of 316L SS, which is comparable to what other authors observed [ 13 ]. In addition, the presence of Ag did not cause any decrease in hemocompatibility of the base alloy, similarly to what was reported by other authors on pure Fe [ 44 , 45 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Hemocompatibility tests showed that the studied TWIP steels have similar performances to those of 316L SS, which is comparable to what other authors observed [ 13 ]. In addition, the presence of Ag did not cause any decrease in hemocompatibility of the base alloy, similarly to what was reported by other authors on pure Fe [ 44 , 45 ].…”
Section: Discussionsupporting
confidence: 88%
“…This alloy family possesses equivalent mechanical properties to Co-Cr alloys [ 9 , 10 ] and their high amount of Mn stabilizes austenite at room temperature [ 11 ], whose paramagnetic behavior favors post-implantation imaging [ 2 ]. At the same time, the degradation behavior of such steels is inappropriate in the long-term: several in vitro and in vivo studies found that a stable corrosion layer is formed during the first weeks of implantation, reducing corrosion rate [ [12] , [13] , [14] ]. The addition of Ag to TWIP steels showed the ability to accelerate the short-term corrosion of these alloys [ [15] , [16] , [17] ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding biosafety of Fe-based materials, previous in vivo studies revealed no iron excess or organ damage caused by iron-based degradation products, indicating acceptable biocompatibility ( Peuster et al, 2006 ; Waksman et al, 2008 ; Wu et al, 2013 ). According to ISO 10993-4, Fe-based materials exhibited excellent blood compatibility with a hemolysis rate below 5% as well as anti-platelet adhesion ( Schinhammer et al, 2013 ; Verhaegen et al, 2019 ). However, some previous in vivo studies demonstrated that Fe-based implants within physiologic environments had a relatively slow degradation rate and formed insoluble degradation products, adversely affecting the local tissue remodeling ( Pierson et al, 2012 ; Drynda et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Assessing blood compatibility is a fundamental part of defining a material as biocompatible. Blood flow across the stent surface could induce erythrocyte rupture, adsorption of plasma proteins leading to platelet activation, and finally, activation of the intrinsic coagulation pathway, resulting in thrombin activation [50]. Some studies have defined Fe-based alloys as biocompatible degradable biomaterials exclusively based on cytotoxicity results, without assessing hemolysis, platelet adhesion or coagulation [18,51].…”
Section: Amentioning
confidence: 99%